Factors that influence the quality of final impressions for fixed dental prostheses in Nairobi, Kenya - Gikunda, Mary K.; Osiro, Olivia A.; Simila, Hazel O.; Alasow, Kassim B.; Nyaga, James M. (International Journal of Dental Materials, 2023)
Background: Good quality dental impressions free of air bubbles, voids, steps, drags, streaks and tears are a pre-requisite for the fabrication of well-fitting fixed dental prostheses (FDP). The quality of impressions is dependent on clinician and material factors. Aim: To evaluate factors that influence the quality of final impressions for FDP in Nairobi, Kenya. Methods: In this cross-sectional study, 234 impressions received by five dental laboratories were analyzed. The study collected information on the type of tray, impression material, technique, type of prostheses, and clinically detectable errors, including voids, inadequate material at margins, tears, steps, drags, and streaks. Impression quality was the outcome assessed as good, fair, or poor by two investigators. The independent variables influencing impression quality included clinician specialty, experience, impression material, technique, and tray type. Results: Inter-rater agreement was 96.8% (p<0.001). Clinician experience ranged between 1-45yrs, median 13.5yrs and mean 8.39±11.96yrs. The majority were GPs, 80.8% while restorative dentists were 11.5% and other specialists, 7.7%. Most impressions were non-aqueous elastomers, 97.9% employing dual-viscosity technique, 75.6%. Impression trays included stock metal, 60.3%, stock plastic, 34.2%, and custom, 5.5%. Impression quality was good, 24.8%, fair, 37.2% or poor, 38.0%. Cumulatively, 74.5% impressions had bubbles/voids, 53.0% tears and 43.2% poor margins. Clarity of margins was associated with clinician specialty, (Fisher’s exact=9.372, p=0.047), and impression technique with impression quality, (Pearson’s ?2 = 6.385, p=0.041). Compared to restorative specialists, estimated odds of other specialists producing poor margins was 5.71, 95%CI 1.55,21.06, Wald ?2=5.24, p=0.009 while for GPs, the estimated odds was 2.19, 95%CI 0.88, 5.43, Wald ?2 = 2.86, p=0.09. Compared to dual viscosity, estimated odds of monophase giving a poor-quality impression was 1.52, 95%CI 0.83,2.78, Wald ?2 = 1.52, p=0.18. Conclusion: Most impressions were good or fair hence acceptable. Quality of impressions was influenced by clinician specialty and impression technique.